ANALYSIS OF PRODUCT VARIANTS, SALES PROMOTION, AND PRICE POLICY ON INCREASING REVENUE AT PRIMA FRESHMART TULANGAN - Handini Kurnia Damayanti; supardi supardi; Detak Prapanca (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the influence of Product Variants (X1), Sales Promotion (X2), and Price Policy (X3) on Revenue Increase (Y) in Prima Freshmart Tulangan Sidoarjo. This research is research that uses a quantitative approach by using a type of descriptive research with SEM-PLS as a data analysis method with the Smart-PLS 3.0 program. The sample selection method used is non-probability sampling while the sampling technique used is by random sampling technique. The population in this study is consumers who purchase products from Prima Freshmart Tulangan with a total of 100 respondents. The data was collected by distributing questionnaires to respondents. Based on the results of the study, it was shown that the Product Variant variable (X1) did not have a positive and significant effect on Revenue Increase (Y) while the Sales Promotion variable (X2) and Price Policy (X3) had a positive and significant effect on sales increase. With this in mind, riots must pay attention to the products that will be marketed which will later affect the increase in income.